The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Beyond the Trail—Understanding Non‐Native Plant Invasions in Mountain Ecosystems - Agustina Barros; Eduardo Fuentes Lillo; Valeria Aschero; Aníbal Pauchard; María Alisa Alvarez; Ronja Wedegärtner; Jan Clavel; Jana Müllerová; Jan Pergl; Shengwei Zong; Michaela Vítková; Tereza Klinerová; et al. (Global Ecology and Biogeography, 2025)
Aim We aimed to examine the abiotic, biotic and anthropogenic drivers of non‐native plant species distribution along hiking trails in mountainous regions. Location Nine mountain regions across six continents, including North America (USA), South America (Argentina and Chile), Europe (Sweden, Norway, Czech Republic), Africa (South Africa), Asia (China) and Oceania (Australia). Time Period Data were collected between 2016 to 2022 during the summer season. Major Taxa Studied Vascular plants. Methods We implemented a standardised sampling design (MIREN trail survey) with T‐shaped sample sites placed parallel to trails and perpendicular to adjacent vegetation. We examined the main drivers (abiotic, biotic and anthropogenic factors) affecting non‐native species' presence, richness and cover. Results At the global scale, abiotic (climatic) variables explained most of the variation in non‐native species richness. In contrast, biotic factors were the most important for the presence and cover of non‐native plants. Anthropogenic factors, including distance to the trail, use intensity and livestock grazing, were also important but to a lesser extent than the main factors. While the total number of non‐native species differed across regions, the patterns explaining plant invasions were consistent. Main Conclusions Our regional study identified mountain trails that are particularly vulnerable to plant invasions. Our findings suggest that under future scenarios of climate change, increased anthropogenic pressure and heightened livestock activity, the presence of non‐native species beyond trail edges may become more frequent. This highlights the need to restrict off‐trail activities in areas of high conservation value.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris - Shawn Larson; Roderick B. Gagne; Jim Bodkin; Michael J. Murray; Katherine Ralls; Lizabeth Bowen; Raphael Leblois; Sylvain Piry; Maria Cecilia Penedo; M. Tim Tinker; Holly B. Ernest (Marine Mammal Science, 2021)
Sea otters, Enhydra lutris , were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, population structure, and connectivity between remnant and reintroduced populations. Average genetic diversity within populations was similar: observed heterozygosity 0.55 and 0.53, expected heterozygosity 0.56 and 0.52, unbiased expected heterozygosity 0.57 and 0.52, for reintroduced and remnant populations, respectively. Sea otter population structure was greatest between the Northern and Southern sea otters with further structuring in Northern sea otters into Western, Central, and Southeast populations (including the reintroduced populations). Migrant analyses suggest the successful reintroductions and growth of remnant groups have enhanced connectivity and gene flow between populations throughout many of the sampled Northern populations. We recommend that future management actions for the Southern sea otter focus on future reintroductions to fill the gap between the California and Washington populations ultimately restoring gene flow to the isolated California population.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Influence of occupation history and habitat on Washington sea otter diet - Jessica R. Hale; Kristin L. Laidre; M. Tim Tinker; Ronald J. Jameson; Steven J. Jeffries; Shawn E. Larson; James L. Bodkin (Marine Mammal Science, 2019)
Habitat characteristics are primary determinants of nearshore marine communities. However, biological drivers like predation can also be important for community composition. Sea otters ( Enhydra lutris ssp.) are a salient example of a keystone species exerting top‐down control on ecosystem community structure. The translocation and subsequent population growth and range expansion of the northern sea otter ( Enhydra lutris kenyoni ) in Washington State over the last five decades has created a spatio‐temporal gradient in sea otter occupation time and density, and acts as a natural experiment to quantify how sea otter population status and habitat type influence sea otter diet. We collected focal observations of sea otters foraging at sites across the gradient in varying habitat types between 2010 and 2017. We quantified sea otter diet composition and diversity, and long‐term rates of energy gain across the gradient. We found that sea otter diet diversity was positively correlated with cumulative sea otter density, while rate of energy gain was negatively correlated with cumulative density. Additionally, we found that habitat type explained 1.77 times more variance in sea otter diet composition than sea otter cumulative density. Long‐term diet studies can provide a broader picture of sea otter population status in Washington State.

Decrease in Sightings of Sixgill Sharks, Hexanchus griseus, in Elliott Bay, Seattle, WA, United States, a Comparison Between 2003–2005 and 2008–2015 - Denise Griffing; Jeff Christiansen; Joel Hollander; Tim Carpenter; Shawn Larson (Frontiers in Marine Science, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

In vitro-Zytotoxizitätsanalyse mit humanen Primärhepatozyten - Brad Larson; Tim Moeller; Grant Cameron; Joël Mailliet (BIOspektrum, 2014)

A flexible spatio-temporal model for air pollution with spatial and spatio-temporal covariates - Johan Lindström; Adam A. Szpiro; Paul D. Sampson; Assaf P. Oron; Mark Richards; Tim V. Larson; Lianne Sheppard (Environmental and Ecological Statistics, 2014)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Prenatal ambient air pollution exposure and small for gestational age birth in the Puget Sound Air Basin - Sheela Sathyanarayana; Chuan Zhou; Carole B. Rudra; Tim Gould; Tim Larson; Jane Koenig; Catherine J. Karr (Air Quality, Atmosphere & Health, 2013)